บทบาทการส่งเสริมดนตรีไทยของพลตรีประพาศ ศกุนตนาค - ปรมินทร์ เต็มพร้อม (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study aimed to study the personal history of Major General Prapas Sakuntanaga and his roles in supporting Thai traditional music. The findings revealed that Major General Prapas Sakuntanaga was born in a family which was satisfied with Thai traditional music. Therefore, he was interested in Thai traditional vocal music. He followed vocal music by Khunying Phaithoon Kittiwan and Kru Niao Duriyaphan’s vocal music style. With the ability in singing beautifully and Sepha performance, he was chosen as a Sepha performer who sang drama songs of the Royal Thai Army Radio and Television 7. Moreover, he was always invited to sing Thai songs in many important events.     Major General Prapas Sakuntanaga soldiered in the Signal Department. He worked as an announcer to report news on several important occasions at the Royal Thai Army Radio and Television 5. Furthermore, he  was an actor and a Thai singer; thus, he was widely well-known. As a distinguished supporter of Thai traditional music, there were many people  who followed his performance and applied to be his students. In addition, he played as an important role in supporting Thai traditional music and spreading Thai vocal music. Importantly, he was such a person who relayed basic knowledge about Thai singing, Krubsepha, and  how to invent Krubsepha to his students. Moreover, he was one of the founders of the Headquarters of Siamsephanuraksa, an organization supporting Thai singing, and Krubsepha performance through online platforms.